2002
DOI: 10.1074/jbc.m111612200
|View full text |Cite
|
Sign up to set email alerts
|

Huntingtin-associated Protein 1 Interacts with Hepatocyte Growth Factor-regulated Tyrosine Kinase Substrate and Functions in Endosomal Trafficking

Abstract: Huntingtin-associated protein 1 (HAP1) is a novel protein of unknown function with a higher binding affinity for the mutant form of Huntington's disease protein huntingtin. Here we report that HAP1 interacts with hepatocyte growth factor-regulated tyrosine kinase substrate (Hrs), a mammalian homologue of yeast vacuolar protein sorting protein Vps27p involved in the endosome-to-lysosome trafficking. This novel interaction was identified in a yeast two-hybrid screen using fulllength Hrs as bait, and confirmed by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
101
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(105 citation statements)
references
References 61 publications
4
101
0
Order By: Relevance
“…HAP1 exhibited clusters in the dendrites and axons, in addition to substantial intracellular somatic staining, including large perinuclear structures consistent with the localization of this protein to intracellular compartments such as endosomes and tubulovesicular structures (Fig. 2G), as demonstrated (23)(24)(25)(26). The GABA A R ␥2 subunit appeared as membrane clusters in addition to abundant intracellular aggregates (Fig.…”
Section: Gabaar Endocytosis and Recycling In Neuronssupporting
confidence: 60%
See 2 more Smart Citations
“…HAP1 exhibited clusters in the dendrites and axons, in addition to substantial intracellular somatic staining, including large perinuclear structures consistent with the localization of this protein to intracellular compartments such as endosomes and tubulovesicular structures (Fig. 2G), as demonstrated (23)(24)(25)(26). The GABA A R ␥2 subunit appeared as membrane clusters in addition to abundant intracellular aggregates (Fig.…”
Section: Gabaar Endocytosis and Recycling In Neuronssupporting
confidence: 60%
“…Future studies using loss-of-function approaches should help clarify this issue. Previous studies have shown that HAP1 associates with proteins that participate in vesicular membrane trafficking, including p150 glued , a component of the dynactin complex, essential for the activity of the microtubule motor protein dynein and Hrs early endosomal phosphoprotein involved in the sorting of ubiquitinated membrane proteins (26,(30)(31)(32). Therefore it is tempting to speculate that HAP1 regulates GABA A R endocytic sorting by facilitating interactions with microtubule motors such as dynein or kinesin (30,31,33,34).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…22 Synaptic components are also retrieved from the plasma membrane by endocytosis into REs and can be either reinserted or degraded. 23 As vesicle trafficking events have been implicated in HD, [24][25][26][27][28][29] we decided to investigate whether aggregation of a mutant htt exon-1 fragment in the cytoplasm would affect spine maintenance by interfering with endosomal trafficking. Previous reports have shown a disruption of endocytic trafficking in cells expressing a mutant htt fragment, 28,29 which appears to be mediated by Rab11, a GTPase involved in RE function.…”
mentioning
confidence: 99%
“…Thus, we concluded that Hap1 not only sequesters but also stabilizes Dcaf7 in the cytoplasm by inhibiting its degradation by the UPS. Because Hap1 can protect internalized receptors from lysosomal degradation (11,(29)(30)(31), Hap1 may stabilize its binding partners from subsequent degradation through either the lysosome or UPS.…”
Section: Hap1 Stabilizes the Protein Level Of Dcaf7 By Inhibiting Itsmentioning
confidence: 99%